Psychoterapeuci o klientkach i klientach - płeć społeczno-kulturowa jako kategoria analizy wzorow funkcjonowania kobiet i mężczyzn w procesie psychoterapii = Psychotherapists on their female and male clients: gender as a category for the analysis of patterns of women and men functioning in the process of psychotherapy - Frąckowiak-Sochańska, Monika (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article locates itself within the field of social studies with a special focus on the overlap between sociology and psychology. It attempts to answer the question to what extent the problems affecting the mental health of women and men reflect certain constructions of gender that function in modern society. The empirical basis of the article is data obtained during in-depth interviews with psychotherapists. This data was analyzed in accordance with the rules of the Grounded Theory Method.
Keywords: kobiety; mężczyźni; płeć; zdrowie psychiczne; psychoterapia; women; men; gender; mental health; psychotherapy